ANALYSIS OF HABITUS IN THE SAMBAS TQN CONGREGATION: EDUCATION, ETHICS, AND LOCALITY - Ghozali, Ahmad; Kaweli, Muhafizah (Universitas Tanjungpura, 2025)
This study aims to analyze the formation and manifestation of habitus within the Qadiriyah wa Naqsyabandiyah (TQN) community in Sambas, emphasizing three main dimensions: education, ethics, and locality. This study uses Pierre Bourdieu's Habitus Theory as the primary analytical framework to understand the dialectical relationship between the social structure of the order and the religious actions of its members. The approach used is qualitative with an ethnographic case study design. Data were collected through participant observation during dhikr (remembrance) and religious study activities, in-depth interviews with mursyid (spiritual guides) and active TQN members, and documentation of teaching texts and socio-religious activities. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that the habitus of TQN members is formed through an educational process that instills the values of adab (adab), spiritual discipline, and emotional closeness to the mursyid. Ethics such as tawadhu' (religious tolerance), ikhlas (sincerity), and patience become moral dispositions internalized in the religious practices and social lives of the members. On the other hand, Sambas Malay cultural values provide a local context that reinforces religious symbols, language, and meaning within the community. This study fills a gap in previous research, which rarely integrates Bourdieu's concept of habitus with the dynamics of local Islamic traditions, providing a theoretical contribution to understanding how spiritual education interacts with the cultural context in shaping religious identity. Thus, the habitus of the Sambas TQN is a synthesis of the tarekat's spiritual structure, Islamic ethical values, and local cultural wisdom, forming a model of religious education and a distinctive social character of Malay Islam.